Biochar Enhanced Starch (BES) Gel - Su , Wen Xin (IRC, 2016)
Soil conditioner has been used extensively in the field of agriculture to improve the condition of the soil. This is because over time, the soil would lose its original physical qualities and nutrients. Besides that, by using soil conditioner, poor and previously uncultivated soil could be transformed into a plot of land that is suitable to grow crops. Unfortunately, the current synthetic soil conditioner, polyacrylamide (PAM) is harmless in its form, but it would release a chemical known as acrylamide which is a neurotoxin when applied as soil conditioner. Therefore, crops would be contaminated with the harmful chemical, harming the living beings that consumed the crops. Besides improving the soil condition, soil condition also acted as micro reservoir to supply water during drought season. In this study, tapioca starch polymer is used because it is renewable and biodegradable.